GA as a regulatory link between the showy floral traits color and scent. Issue 1 (6th March 2017) - Ravid, Jasmin; Spitzer‐Rimon, Ben; Takebayashi, Yumiko; Seo, Mitsunori; Cna'ani, Alon; Aravena‐Calvo, Javiera; Masci, Tania; Farhi, Moran; Vainstein, Alexander
Summary: Emission of volatiles at advanced stages of flower development is a strategy used by plants to lure pollinators to the flower. We reveal that GA negatively regulates floral scent production in petunia. We used Agrobacterium ‐mediated transient expression of GA‐20ox in petunia flowers and a virus‐induced gene silencing approach to knock down DELLA expression, measured volatile emission, internal pool sizes and GA levels by GC‐MS or LC–MS/MS, and analyzed transcript levels of scent‐related phenylpropanoid‐pathway genes. We show that GA has a negative effect on the concentrations of accumulated and emitted phenylpropanoid volatiles in petunia flowers; this effect is exerted through transcriptional/post‐transcriptional downregulation of regulatory and biosynthetic scent‐related genes. Both overexpression of GA20‐ox, a GA‐biosynthesis gene, and suppression of DELLA, a repressor of GA‐signal transduction, corroborated GA's negative regulation of floral scent. We present a model in which GA‐dependent timing of the sequential activation of different branches of the phenylpropanoid pathway during flower development may represent a link between the showy traits controlling pollinator attraction, namely color and scent.